2014
DOI: 10.1093/nar/gku831
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-targeted in vivo gene silencing via systemic delivery of cRGD-conjugated siRNA

Abstract: RNAi technology is taking strong position among the key therapeutic modalities, with dozens of siRNA-based programs entering and successfully progressing through clinical stages of drug development. To further explore potentials of RNAi technology as therapeutics, we engineered and tested VEGFR2 siRNA molecules specifically targeted to tumors through covalently conjugated cyclo(Arg-Gly-Asp-d-Phe-Lys[PEG-MAL]) (cRGD) peptide, known to bind αvβ3 integrin receptors. cRGD-siRNAs were demonstrated to specifically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 43 publications
1
60
0
1
Order By: Relevance
“…18 We cultured HUVECs in DMEM and C6 cells in MEM (both media were supplemented with 10% fetal bovine serum) at 37°C with 5% CO 2 . The medium was replaced every 1-2 d, and the growth state of the cells was observed daily through an inverted microscope.…”
Section: Cell Affinity Evaluation Of Cyclic Peptides Cell Culturementioning
confidence: 99%
“…18 We cultured HUVECs in DMEM and C6 cells in MEM (both media were supplemented with 10% fetal bovine serum) at 37°C with 5% CO 2 . The medium was replaced every 1-2 d, and the growth state of the cells was observed daily through an inverted microscope.…”
Section: Cell Affinity Evaluation Of Cyclic Peptides Cell Culturementioning
confidence: 99%
“…Integrin α v β 3 -negative HeLa cells 9 were selected to investigate the effect of the interaction between pepetide and CLD to form nanocomplexes on cell uptake. HeLa cells were incubated with 100 nM CLD/FAM-siRNA for 6 h, and the corresponding results are shown in Figure 5C.…”
Section: Serum Stability Of Sirnamentioning
confidence: 99%
“…8 A common cell-targeting peptide is Arg-Gly-Asp peptide sequence (cRGD), which implement endocytosis by binding to overexpressed integrin αvβ3 receptors on tumor cell surface. 9 Many reports have demonstrated that the transport capacity of siRNAs was significantly improved when siRNAs were covalently conjugated with cRGD peptides. [9][10][11] For example, Alam et al conjugated the divalent, trivalent and tetravalent cRGD to the 3′-terminus of the sense strand of siRNA via thioether bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene therapy involves knocking down or silencing of specific oncogenes, and plays a vital role in treating surface tumors [13,14]. Superoxide dismutase 1 (SOD1) is one of the very effective anti-apoptotic and self-defending genes, and can destroy the free radicals or reactive oxygen species in the human body.…”
Section: Introductionmentioning
confidence: 99%